Spatial variability of organic matter in two mangrove ecosystems in Langkawi, Kedah, Malaysia - ROHAYU RAMLI; FAEZAH PARDI; HARINDER RAI SINGH; MUHAMMAD AKMAL ROSLANI; KHAIRUL NAIM ABD. AZIZ; SHARIR AIZAT KAMARUDDIN (Society for Indonesian Biodiversity, 2024)
Abstract. Ramli R, Pardi F, Singh HR, Roslani MA, Aziz KNA, Kamaruddin SA. 2024. Spatial variability of organic matter in two mangrove ecosystems in Langkawi, Kedah, Malaysia. Biodiversitas 25: 329-336. Organic matter is a crucial factor influencing mangroves' structure and species composition. The present study aimed to assess and compare the organic matter content in the sediment of Pulau Dayang Bunting and Sungai Kilim mangroves ecosystem in Langkawi, Kedah. The spatial variation of the organic matter contents was measured from the sediment at different zones in a line transect at each location. The mean of organic matter content recorded in the Pulau Dayang Bunting mangroves community was recorded from 13.67% to 15.74% and 13.06% to 16.57% in the Sungai Kilim mangrove community which were classified in the medium category. Results of Two-way ANOVA analysis revealed significant differences in the organic matter content between mangroves communities and only organic matter content in Station 2 was significantly different at the lower, middle, and upper zones (ANOVA one way, P<0.05). Only salinity has a negative correlation with the organic matter content in the study area (r (34) = [-0.41], p = [0.014]). The upper zones exhibited a greater concentration of organic matter due to enhanced accumulation facilitated by the vertical water mixing. Mangroves age, vegetation density, salinity, and sediment types are also crucial factors in maintaining organic matter content in the mangrove ecosystem.